2017
DOI: 10.13189/ujm.2017.050104
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction, Organizational Commitment, and Organizational Citizenship Behaviour in State-owned Banking

Abstract: Organization need to develop its human resources in a way that can build the high level of organizational citizenship behaviour (OCB). Job satisfaction and organizational commitment can became an important factor which affecting OCB. The aim of this study is to identify the mediating role of organizational commitment in the relationship between job satisfaction and OCB. The samples were derived from a survey using 39 items questionnaire distributed to the 320 employees of a state-owned banking in Bandung, Indo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 34 publications
3
24
1
3
Order By: Relevance
“…However, job satisfaction does not affect OCB. This is different from previous research which concludes that job satisfaction has positive implications (Fitrio et al, 2019;Heriyadi et al, 2020;P Prasetio et al, 2017;Yuliani & Katim, 2017). This research, however, does not support the implications of job satisfaction on implementing positive behavior through OCB, but it indirectly increases OCB with a percentage of 15%.…”
Section: Discussioncontrasting
confidence: 99%
“…However, job satisfaction does not affect OCB. This is different from previous research which concludes that job satisfaction has positive implications (Fitrio et al, 2019;Heriyadi et al, 2020;P Prasetio et al, 2017;Yuliani & Katim, 2017). This research, however, does not support the implications of job satisfaction on implementing positive behavior through OCB, but it indirectly increases OCB with a percentage of 15%.…”
Section: Discussioncontrasting
confidence: 99%
“…These differences in attitudes according to different age groups played contributory roles in determining significant differences in recognition and overall JS. Furthermore, the JS is the attitude (Prasetio et al, 2017) which is influenced by the age groups of teachers (Imam, 1990) and it enhances their performances and academic achievements (Iqbal et al, 2016) in schools.…”
Section: Age Group: Determinant Of Job Satisfactionmentioning
confidence: 99%
“…The research conducted among bank employees in Indonesia found a direct and indirect relationship between organizational citizenship behavior and job satisfaction. It has been proposed to develop human resources in organizations to form a high degree of organizational citizenship behavior (Prasetio, 2017). Yadav and Gupta's 2017 study of the Indian tourism industry found that organizational fairness, job satisfaction, and organizational citizenship behavior were not mediated by organizational trust.…”
Section: Relationship Between Organizational Citizenship and Job Satisfactionmentioning
confidence: 99%